Covid-19, a wake up call for waqf institution - Mohamad, Nor Asiah (New Straits Times Press (M) Bhd, 2020)
Covers about the importance of Waqf in Providing Solutions during Emergency. It is not only a religious institution, but also a social institution providing assistance for the people in need in sustainable manner.